2022
DOI: 10.1002/mde.3603
|View full text |Cite
|
Sign up to set email alerts
|

Do institutional framework and its threshold matter in the sensitivity of CEO pay to firm performance? Fresh insights from an emerging market economy

Abstract: This study examines the role of institutional quality and its threshold in the sensitivity of CEO pay to firm performance in an emerging market economy, using a generalized method of moments, Driscoll and Kraay's nonparametric covariance matrix estimator, and robust dynamic panel threshold. Bureaucratic quality and corruption control weaken performance‐based pay for CEOs, while law and order strengthen it. The overall institutions allow boardroom backscratching which biases executive compensation contracts. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 137 publications
0
8
0
Order By: Relevance
“…Strong evidence of CD indicates a high level of rivalry and competition among banks, which could stir actions and reactions in the course of performing their functions and operations. This reveals the necessity of incorporating the issues of intertwining and interdependence among banks when designing and implementing policies on the CEO pay–bank performance causal nexus (Olaniyi et al, 2022; Olaniyi et al, 2023). Furthermore, it is clear that banks are not free from intertwining and interdependence in terms of efficiency (cost and technical) and profitability.…”
Section: Discussion Of Empirical Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Strong evidence of CD indicates a high level of rivalry and competition among banks, which could stir actions and reactions in the course of performing their functions and operations. This reveals the necessity of incorporating the issues of intertwining and interdependence among banks when designing and implementing policies on the CEO pay–bank performance causal nexus (Olaniyi et al, 2022; Olaniyi et al, 2023). Furthermore, it is clear that banks are not free from intertwining and interdependence in terms of efficiency (cost and technical) and profitability.…”
Section: Discussion Of Empirical Findingsmentioning
confidence: 99%
“…This competition tends to spur executive compensation packages and incentives of one bank to influence that of others in the industry (Bocharova & Rymanov, 2022). This portrays that banks' executive compensation contracts are not independent, as it is implicitly assumed in the existing research (Olaniyi et al, 2022; Olaniyi et al, 2023). Thus, a bank will consider other banks' executive compensation contracts when deciding how much to pay their executives to remain competitive in the hunt for vibrant and promising CEOs.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Besides, these banks are not independent in terms of profitability, efficiency, and size. It is revealed that all the extant studies on the causality between firm size and profitability/efficiency must have overestimated their models by ignoring the issues of CD in their empirical analyses (Olaniyi, Young, et al, 2022). This justifies the adoption of Dumitrescu and Hurlin's (2012) approach to Granger non‐causality, which perfectly captures and deals with the issue of CD.…”
Section: Presentation and Discussion Of Findingsmentioning
confidence: 99%
“…This assumption is practically unrealistic in the real competitive world. In many ways, firms are intertwined and interdependent in their functions and operations (Olaniyi, Young, et al, 2022). Growth in size of a listed firm in an industry may constitute a big threat to other firms and it could incite actions and reactions.…”
Section: Introductionmentioning
confidence: 99%